Fuzheng Quxie Decoction Ameliorates Learning and Memory Impairment in SAMP8 Mice by Decreasing Tau Hyperphosphorylation. (20th December 2017) - Yang, Yang; Jia, Xingxing; Feng, Jianchao; Wang, Zhiyong; Cao, Yu; Liu, Jiangang; Li, Hao
Abstract : Hyperphosphorylation of the microtubule-associated protein, tau, is critical to the progression of Alzheimer's disease (AD). Fuzheng Quxie Decoction (FQD), a Chinese herbal complex, is an effective clinical formula used to treat AD. In the current study, we employed high-performance liquid chromatography and liquid chromatography tandem mass spectrometry to identify the components of FQD. Three major components (ginsenoside Rg1, ginsenoside Re, and coptisine) were detected in the brain of FQD-fed mice, indicating their ability to cross the blood-brain barrier. We further evaluated the efficacy of FQD on Senescence-Accelerated Mice Prone-8 (SAMP8) mice. FQD significantly ameliorated learning and memory deficits in SAMP8 mice on the Morris Water Maze, decreasing escape latency (p < 0.0 1 ) and increasing swim time within the original platform-containing quadrant (p < 0.05 ). Further, FQD increased the number of neurons and intraneuronal Nissl bodies in the hippocampal CA1 region. FQD also decreased the expression of phosphorylated tau protein and increased the expression of protein phosphatase 2A (PP2A) and the N-methyl-D-aspartate receptor subunit, NR2A (p < 0.01 ). Our results indicate that FQD improves the learning and memory ability of SAMP8 mice. Moreover, our findings suggest that the protective effect of FQD is likely mediated through an inhibition of hippocampal tau hyperphosphorylation via NMDAR/PP2A-associated proteins.